DISSEMINATED HISTOPLASMOSIS AS AIDS PRESENTATION. CASE REPORT AND COMPREHENSIVE REVIEW OF CURRENT LITERATURE - Paola Zanotti; Claudia Chirico; Maurizio Gulletta; Laura Ardighieri; Salvatore Casari; Eugenia Quiros Roldan; Ilaria Izzo; Gabriele Pinsi; Giovanni Lorenzin; Fabio Facchetti; Francesco Castelli; Emanuele Focà (Mediterranean Journal of Hematology and Infectious Diseases)
Progressive disseminated histoplasmosis (PDH) is an AIDS-defining illness with a high lethality rate if not promptly treated. The wide range of its possible clinical manifestations represents the main barrier to diagnosis in non-endemic countries. Here we present a case of PDH with haemophagocytic syndrome in a newly diagnosed HIV patient and a comprehensive review of disseminated histoplasmosis focused on epidemiology, clinical features, diagnostic tools and treatment options in HIV-infected patients.